Otium vs. Negotium as the Foundation of the Concept of Solitude in Petrarch’s Philosophical Works - Elena CHIOREAN (TREZBURCĂ) (Studia Universitatis Babeș-Bolyai. Philosophia, 2023)
The concept of solitude, as elaborated by Petrarch in the treatise De vita solitaria, develops on the antagonistic structure of the concepts otium and negotium. These, in turn, contain notions and intellectual approaches found both in Latin Antiquity and in the Middle Ages, which attribute to loneliness a special dynamism by joining it with several other concepts such as: will, freedom and friendship. Each historical stage has a specific approach to the notions of otium and negotium, and in this sense Petrarch’s contribution can be considered significant, even if not entirely new, because he attempts a plenary approach to the idea of solitude.